The effect of leisure activity golf practice on motor imagery: an fMRI study in middle adulthood - Bezzola, Ladina; Mérillat, Susan; Jäncke, Lutz (Frontiers in Human Neuroscience, 2012)
Much is known about practice-induced plasticity of the motor system. But it is not clear whether the activity in the motor network induced by mental motor imagery is influenced by actually practicing the imagined motor tasks. In a longitudinal study design with two measurement time-points, functional magnetic resonance imaging (fMRI) was used to explore dynamic changes in the brain in response to training of highly complex movements by participants of 40 to 60 years of age. The investigated motor learning task entailed golf training practiced by novices as leisure activity. Additionally, data from an age and sex-matched control group without golf training was collected. Results show increased hemodynamic responses during mental rehearsal of a golf swing in non-primary cortical motor areas, sub-cortical motor areas, and parietal regions of the novice golfers and the control subjects. This result complements previous mental imagery research that shows involvement of motor areas during mental rehearsal of a complex movement, especially in subjects with low skill level. More importantly, changes were only found between the two measurement time-points in the golf novice group with a decrease in hemodynamic responses in non-primary motor areas after the 40 hours of golf practice. Thus, the results indicate that a complex physical leisure activity induces functional neuroplasticity in the seldom studied population of middle-aged adults, and that this effect is evident during mental rehearsal of the practiced task. This finding supports the idea that (a) a skill improvement is associated with a modified activation pattern in the associated neuronal network that can be identified during mental rehearsal of the practiced task, and that (b) a strict training protocol is not necessary to induce functional neuroplasticity.